2020
DOI: 10.1111/ipd.12612
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, prospective, randomized trial of pain and discomfort during maxillary expansion: Leaf expander versus hyrax expander

Abstract: BackgroundPain suffered by the young patient is the most frequent symptom during orthodontic treatment and is the one that most frightens children and causes worry in their families.AimTo investigate pain perception and function impairment during the first week of activation of two palatal expansion screws.DesignA total of 101 subjects were randomly divided into two groups: RME group included patients treated with the standard hyrax expansion screw and LEAF group included patients treated with Leaf Expander ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 15 publications
0
50
0
Order By: Relevance
“…Moreover, it was demonstrated by Ugolini et al [62] constant forces exerted by the NiTi spring during maxillary expansion allow to avoid most of the pain that occurs at the beginning of the activation of a RME.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was demonstrated by Ugolini et al [62] constant forces exerted by the NiTi spring during maxillary expansion allow to avoid most of the pain that occurs at the beginning of the activation of a RME.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first randomized controlled trial assessing and comparing the levels of pain, discomfort, and various functional impairments between a removable slow maxillary expander and a bonded rapid maxillary expander in the treatment of skeletal maxillary constriction in growing patients between the ages of 12 and 16. Some researchers have reported that maxillary expansion has caused greater pain and discomfort at such ages in comparison with younger children between the ages of nine and twelve [ 21 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was determined using Minitab® Version 17 (Minitab Inc., State College, Pennsylvania, USA). It was assumed that the smallest detectable difference in pain levels between the two groups was 1 cm on a VAS (with a standard deviation of 1.2 from a previous study) [ 21 ]. Using an independent-samples t-test with a significance level of 5% and a power of 80%, 24 patients were required in each group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations